2022
DOI: 10.1108/ebhrm-05-2021-0097
|View full text |Cite
|
Sign up to set email alerts
|

The bright side of entitlement: exploring the positive effects of psychological entitlement on job involvement

Abstract: PurposeAlthough the sense of entitlement was traditionally associated with a range of maladaptive personality characteristics, the purpose of the current study is to take an initial step to explore a positive implication of psychological entitlement.Design/methodology/approachThe target population for this study comprises employees from various industries in Taiwan. To examine the research hypotheses, structural equation modeling techniques were employed to perform a mediation analysis and conditional process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Similarly, entitlement predicted more self-reported OCBs and was related to fewer self-reported CWBs. Contradictory to previous findings, Lin et al (2022) assumed that psychological entitlement is positively related to job involvement.…”
Section: Employee Entitlement and Work Behaviormentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, entitlement predicted more self-reported OCBs and was related to fewer self-reported CWBs. Contradictory to previous findings, Lin et al (2022) assumed that psychological entitlement is positively related to job involvement.…”
Section: Employee Entitlement and Work Behaviormentioning
confidence: 86%
“…However, there are still many researchers using measures based on trait conceptualization (e.g. Lin et al, 2022;Joplin et al, 2021;Schwarz et al, 2021;Irshad, 2021;Cerritos, 2020). Using measures based on state conceptualization as Westerlaken et al's Measure of Employee Entitlement (2017) is still not as common as their advantages might indicate (e.g.…”
Section: Employee Entitlementmentioning
confidence: 99%
“…It is also possible to further discuss the conditions under which psychological entitlement can be lessened, as well as the conditions under which psychological entitlement's detrimental effects can be mitigated. The relationship between psychological entitlement and good conduct can also be investigated, as research has shown that psychological entitlement might increase job involvement by raising career ambitions [119].…”
Section: Theoretical Implicationsmentioning
confidence: 99%